2010
DOI: 10.1093/schbul/sbq057
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Performance in Older Patients With Schizophrenia: A Meta-Analysis of Cross-sectional and Longitudinal Studies

Abstract: Objective: Cognitive deficits are among the most reliable predictors of functional impairment in schizophrenia and a particular concern for older individuals with schizophrenia. Previous reviews have focused on the nature and course of cognitive impairments in younger cohorts, but a quantitative meta-analysis in older patients is pending. Method: A previously used search strategy identified studies assessing performance on tests of global cognition and specific neuropsychological domains in older patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
79
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 48 publications
11
79
1
4
Order By: Relevance
“…Although some research groups found evidence of progressive impairment in executive function in relation to illness course, others described a static nature of the cognitive deficit in schizophrenia (Freedman and Brown, 2011). Most of the earlier reviews and meta-analyses considered executive dysfunctions as a core feature of schizophrenia, present at the onset of the disorder and remaining stable over the course of the illness (Szoke et al, 2008;Irani et al, 2011;Bora and Murray, 2014). Our results are not consistent with previous findings, as we observed an association between WCST performance and illness duration.…”
Section: Interactions Between Doi Gray Matter and Executive Functioningcontrasting
confidence: 99%
See 1 more Smart Citation
“…Although some research groups found evidence of progressive impairment in executive function in relation to illness course, others described a static nature of the cognitive deficit in schizophrenia (Freedman and Brown, 2011). Most of the earlier reviews and meta-analyses considered executive dysfunctions as a core feature of schizophrenia, present at the onset of the disorder and remaining stable over the course of the illness (Szoke et al, 2008;Irani et al, 2011;Bora and Murray, 2014). Our results are not consistent with previous findings, as we observed an association between WCST performance and illness duration.…”
Section: Interactions Between Doi Gray Matter and Executive Functioningcontrasting
confidence: 99%
“…However, given that this study considered together both WCST and Halstead Category Test performances, these differences are difficult to interpret. Another recent meta-analysis (Irani et al, 2011) reported that greater global cognitive impairment was associated with shorter DoI and that later age of onset was not associated with specific neuropsychological domains. There was not a specific analysis for WCST.…”
Section: Clinical Characteristics and Behavioral Performancementioning
confidence: 97%
“…However, longitudinal neuropsychological studies in first-episode and established schizophrenia and UHR have not found evidence of cumulative cognitive decline (Szöke et al 2008;Bonner-Jackson et al 2010;Irani et al 2011;Bora & Murray, 2014). In these patient samples, cognitive deficits are stable or even slightly improved at follow-up.…”
Section: Illusion Of Progression In Schizophreniamentioning
confidence: 92%
“…This would argue that a system should be in place to ensure that a patient can get the treatment that they require, even if they do not consent. It could be argued that the use of CTOs provides such a mechanism and aids in preventing the patient from becoming a victim of their own illness, owing to a repeating pattern of illness relapse, deterioration in social functioning and residual cognitive impairment (Heaton et al 2001;Irani et al 2011). The use of a beneficence approach holds the patients' best interests as a central tenet in deciding the most appropriate treatment programme for them to allow for the restoration of their decision-making capacity.…”
Section: Ethical Considerationsmentioning
confidence: 99%